A green prescription: integrating environmental sustainability in urology guidelines - Herrmann, Alina; van Veen, Felice E. E.; Blok, Bertil F. M.; Watts, Kara L. (European urology focus, 2023)
Against the background of the climate crisis, there is an urgent need to include environmental sustainability recommendations in clinical practice guidelines. We highlight five domains for which suitable recommendations could help in mitigating the environmental impact of urology practice. Patient summary: Climate change is an urgent issue that requires global action. Guidelines published by urological societies should include recommendations for minimizing the impact of urology practice on the environment. (c) 2023 European Association of Urology. Published by Elsevier B.V. All rights reserved.